Symptomatic neurosyphilis in HIV-negative patients: a retrospective cohort study - Chen, Qiaoer; Wu, Weiqi; Wang, Lu; Huang, Honghong; Wang, Lingxing (Frontiers in Public Health, 2025)
IntroductionNeurosyphilis does not necessarily involve progressive invasion from interstitial to parenchymal nerve tissue. Few studies have focused on human immunodeficiency virus (HIV)-negative patients with symptomatic neurosyphilis, and the clinical outcomes and factors influencing the outcomes are unclear. Therefore, in this study, we aimed to compare the characteristics and clinical outcomes of interstitial and parenchymal neurosyphilis following treatment in HIV-negative patients with symptomatic neurosyphilis.MethodsWe conducted a retrospective analysis of the clinical characteristics, laboratory results, neuroimaging findings, treatment regimens, and outcomes at discharge of HIV-negative patients admitted to our hospital with symptomatic neurosyphilis between May 2013 and May 2023.ResultsOf the 142 patients, the mean age was 56.6 ± 11.4 years, with 111 (78.2%) being men. The predominant clinical manifestations included psychological disorders, cognitive decline, and cranial nerve disorders. Overall, 134 (94.4%) patients had elevated cerebrospinal fluid (CSF) cell counts, 113 (79.6%) had elevated protein levels, and 22/133 (16.5%) had elevated intracranial pressure. During hospitalization 113 patients (87.6%) were treated with intravenous penicillin and 13 (10.1%) were treated with ceftriaxone. Furthermore, 62 (43.7%) and 80 (56.3%) patients had interstitial and parenchymal types of neurosyphilis, respectively. Patients with the parenchymal type were younger and had higher platelet-to-lymphocyte ratio (PLR) and lower lymphocyte-to-monocyte ratio (LMR). Overall, 126 (88.7%) patients completed anti-syphilitic treatment prior to discharge, with 111 (88.1%) showing poor outcomes.DiscussionAn elevated CSF protein level and the parenchymal type were associated with poor outcome. This study revealed that clinical manifestations of neurosyphilis vary, and that the majority of patients had elevated CSF cell and protein levels and a normal intracranial pressure. The PLR was higher and the LMR was lower in the parenchymal type than in the interstitial type. Only a small proportion of patients had favorable outcomes. CSF protein level and parenchymal type may be risk factors for poor prognosis.